Treatment Outcome of a β-hCG Secreting Intracranial Germ Cell Tumor in an Adult Filipino using Definitive Chemotherapy followed by Radiotherapy: A Case Report - Gan, Florence Rochelle; Gomez, Maria Honolina; Tapispisan, Julie Ann (Journal of the ASEAN Federation of Endocrine Societies, 2022)
We report a case of a 24-year-old Filipino male who complained of general weakness, polydipsia, weight loss, bitemporal headaches, loss of libido and behavioral changes. Endocrine work-up revealed neurogenic diabetes insipidus and panhypopituitarism. Brain MRI showed multiple intracranial tumors in the left frontal lobe, pineal and suprasellar region with moderate non-communicating hydrocephalus. Intracranial mass biopsy with ventriculo-peritoneal shunting was done. Histopathology of the mass and CSF revealed a germinoma. He underwent chemoradiotherapy while on maintenance hormone replacement.